Influence of eddies and tropical cyclone heat potential on intensity changes of tropical cyclones in the North Indian Ocean. Issue 2 (15th July 2021) - Jangir, B.; Swain, D.; Ghose, S.K.
Abstract: Eddies are known to play a crucial role in the sudden intensification of tropical cyclones. In this study, Sea Level Anomaly (SLA) data from satellite altimetry is utilized to investigate the role of eddies on tropical cyclones intensification in the North Indian Ocean (NIO) basin. SLA data obtained from Archiving Validation and Interpretation of Satellite Data in Oceanography (AVISO), Tropical Cyclone Heat Potential (TCHP) from National Remote Sensing Centre (NRSC) and cyclone intensity data from Indian Meteorological Department (IMD) have been utilized to analyse and understand the impact of TCHP and eddies on 60 tropical cyclones in the NIO spanning the years 2001–2018. Out of these 60 cyclones, 38 were formed in the Bay of Bengal (BoB) and 22 in the Arabian Sea (AS). From the analysis, it is found that nearly 40% cyclones are affected by Warm Core Eddy (WCE) generally intensifying them, 30% are influenced by Cold Core Eddy (CCE) that generally reduce cyclone intensities and the rest 30% are affected by TCHP variations (in the absence of eddies) in the NIO region during the study period. Cyclones which do not follow the established trend of intensifying due to WCEs or increasing TCHP; and diminishing owing to CCEs or TCHP decrease were found to be governed primarily by the Translational Speed of the cyclones. WCE are mostly present during the pre-monsoon season in the NIO (both BoB and AS). This analysis confirms that consideration of the underlying eddies in the cyclone track represented by SLA, TCHP variations, Translational Speed of cyclones and the ocean barrier layer are key factors that must be considered in forecasting cyclone intensity and track.